Chilli row collector / Najib Mohamad.M … [et al.] - Mohamad.M, Najib; .S, Nurul Atikah; .A.Z, Muhammad Nashriq; .A.R, Ahmad Irfan; .N, Muhammad Hafiz; .M.N, Nur Wajihah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Chilli cultivation is one of the crops that is significantly profitable in the country. There are so many varieties of chillies including jalapeño, ghost pepper and tabasco pepper. In chilli cultivation, the harvesting process is taking much time as the harvester needs to pick chilli fruits one by one. After identifying the problems that occur in this production, we created a tool to make it easier for workers when harvesting chili. The tool name is Chilli Row Collector which it is a tool that help the labour harvest chilli fruits more easily and efficiently. It is made with some reusable item like bottle tied to the hand and be able to directly temporary store the chilli before moving to the larger storing item like sack. During harvesting the body movement can be reduce and the labourers can comfortably do their job. This can help them avoid further pain or injuries like back pain after doing repeating action for a long time. Thus, this innovation is expected to improve the efficiency and time consumption in the chilli cultivation as well as it can improve the profitability obtained by the producers.